PENUNTUTAN TERHADAP PERDAGANGAN PEREMPUAN DAN ANAK DI KEJAKSAAN NEGERI MAKASSAR - Disa Haifa Izdihar (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to find out and analyze the implementation of prosecution in the criminal act of trafficking in women and children in the city of Makassar, as well as the factors that hinder the implementation of the prosecution. Research uses primary data through interviews. Secondary data is done through collecting data, documents and relevant legislation. The data obtained was processed and analyzed using qualitative analysis. The results of the study show that the prosecution of the crime of trafficking in women and children in the Makassar District Prosecutor's Office is experiencing obstacles in the process of prosecuting criminal acts such as proofs. Factors that inhibit the internal factors, including legal factors themselves, law enforcement factors and facilities or facilities. While external factors, including community factors and cultural factors.